2014
DOI: 10.1364/ao.53.002556
|View full text |Cite
|
Sign up to set email alerts
|

Multilevel anisotropic diffractive optical elements fabricated by means of stepping photo-alignment technique using photo-cross-linkable polymer liquid crystals

Abstract: Multilevel anisotropic diffractive optical elements (DOEs), in which digitized spatial patterns of optical birefringence are fabricated by means of stepping photoalignment technique, has been demonstrated using photo-cross-linkable polymer liquid crystals (PCLCs). The polarization state of incident light is converted into a different polarization state by diffracting light in the practical, i.e., transparent in visible region and thermally stable, multilevel anisotropic DOEs, and both polarization azimuth and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…In this study, although we used the OCPG as the PG, several kinds of other PGs have been reported so far, such as orthogonal linear PG, 10) multilevel anisotropic diffractive films, 12) and crossed-polarization gratings. 11) Therefore, we can fabricate various types of Fabry-Perot PGs showing unique polarization conversion and diffraction properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, although we used the OCPG as the PG, several kinds of other PGs have been reported so far, such as orthogonal linear PG, 10) multilevel anisotropic diffractive films, 12) and crossed-polarization gratings. 11) Therefore, we can fabricate various types of Fabry-Perot PGs showing unique polarization conversion and diffraction properties.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, we have also studied LCPGs fabricated using a photo-crosslinkable polymer LC (PCLC). [10][11][12][13] PCLC has the features of high transmittance, high stability against environmental temperature, and high anchoring energy, so we developed several types of LCPG such as crossed polarization gratings, 11) multilevel anisotropic diffractive films, 12) and holographic binary grating LC cells. 13) The advantageous features of these LCPGs have led to applications in optical projection, 14) snapshot-type polarimetry, 15) and optical measurement.…”
Section: Introductionmentioning
confidence: 99%
“…A PG is a diffractive optical element in which the in-plane anisotropic orientation varies linearly along the surface and the magnitude of anisotropy is constant [15][16][17][18][19][20][21][22][23]. It is fabricated by methods such as optical orientation by two-flux interference exposure [24], micro-rubbing [25,26], photomasking [27], and direct beam writing [8,28]. In these methods, the diffraction efficiency is improved by increasing the variation in refractive index in the film or the non-uniform structure of the film.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to these characteristics, LCs have been studied as materials for optical elements such as displays and diffraction gratings. [1][2][3][4][5][6][7][8][9][10] An LC lens is an optical element, and several structures have been proposed thus far for the LC lens. One of the conventional structures contains a Fresnel zone type, in which the LC structure is formed to be mutually aligned to two directions in adjacent zones.…”
Section: Introductionmentioning
confidence: 99%